Hemofilia - Baiq nindya annisa putri; Devi Rahmadona (Unram Medical Journal, 2022)
Hemophilia is a hereditary disease characterized by heavy bleeding. This disease presents as minor posttraumatic bleeding or spontaneous bleeding. Hemophilia is caused by abnormalities in the coagulation protein factors. Factor VIII (FVIII) causes hemophilia A, and factor IX (FIX) causes hemophilia B. Hemophilia can be diagnosed through gene sequencing by identifying carrier status. At the time of prenatal, hemophilia can be detected when the fetus is 12 weeks old, but has a risk of miscarriage 0.5-1.0%. Hemophilia is treated by two approaches: management of acute bleeding and prophylaxis. Treatment of hemophilia must pay attention to the dose, schedule, and target level. Hemophilia treatment can use recombinant factor VIII by involving virus inactivation and screening technology which is considered safer. Complications can occur due to the presence of inhibitors of the function of the action of coagulation protein factors, hemophilic arthropathy, and pseudotumor that triggers soft tissue bleeding that has the potential to injure internal organs. Prevention efforts are carried out by keeping patients away from activities that trigger physical bleeding wounds, and ensuring that patients have a normal immune system to receive routine vaccinations.